EuroREGEN - Transnational networks for regenerative development in Europe: A comparative perspective on grassroots mobilisation and policy advocacy - Esteves, A. (Midi du CIRTES, 2021)
EuroREGEN aims to develop a theory of political processes in the field of regenerative development and to bridge academia, practice and policy making through both participatory research methods and outputs targeted at multiple audiences. It will undertake a comparative analysis of how transnational networks of autonomous initiatives working at the scale of the local community Community-Led Initiatives in Europe mobilize within and across national borders and engage public institutions in order to promote favourable institutional environments for regenerative development. EuroREGEN will analyse how GEN, TN and RIPESS mobilize, frame and communicate the policy claims of CLIs at regional, national and European Union levels, and how they transpose responses from public institutions to grassroots level. By mapping, comparing and contrasting processes of institutional communication, relationship-building and policy advocacy in these networks, this project aims to understand the contributions of bioregionalism and solidarity economy to the mainstreaming of regenerative development. It will employ a mixed methodology to explore how the approach to regenerative development taken by these networks and the opportunities and constraints of their relational environments impact: a) The way they identify claims of associated CLIs, frame them and mobilize the resulting information strategically to impact agenda-setting and decision-making in policy environments; b) The actual perceptions that CLIs have of their own needs and relevant policy levers for achieving their aims; c) Networks’ choices of partners and allies within public institutions; d) Networks’ access to decision-makers and gatekeepers in policy environments; e) How networks communicate with policy actors in order to influence meaning-making processes underlying agenda-setting and decision-making; f) How responses from public institutions are transposed to the grassroots level. The focus of the policy analysis will be regional development policies, and energy and climate plans, including: - Negotiation and application of EU Regional Development Funds and Social Funds; - Contributions to the European Green Deal; - 2021-2027 EU Budget; - EU post-Covid-19 economic recovery plan. This project has three goals: - Compare and contrast approaches to framing members’ demands, coalition-building and policy advocacy by the European hubs of the three major networks that promote a regenerative approach to development: Global Ecovillage Network (GEN), Transition Network (TN) and the Intercontinental Network for the Promotion of Social Solidarity Economy (RIPESS). - Understand how the results of such processes are transposed to members, in the form of policy implementation - Compare and contrast how such processes of coalition-building, policy advocacy and policy implementation happen in each of the three networks taken individually, as well as through the umbrella network ECOLISE - European Consortium for Community-led Initiatives on Climate Change and Sustainability.